Zbirka pisnih nalog za bibliotekarski izpit - Knap, Nataša (Zbirka pisnih nalog za bibliotekarski izpit, 2021)
To be able to perform professional librarian work independently, whether in a library, or other organization working in the field of librarianship, the employees are required to pass the national librarianship exam. On the basis of a public mandate, the examinations are organized and conducted by the National and University Library. The collection consists of written assignments prepared by the library employees for the purposes of the examination. A candidate prepares a written paper during the professional training for the examination, which takes place in the library under the guidance and supervision of a tutor. The written assignment for the librarian examination is an independently written dissertation of a selected professional topic referring to the field of librarianship. The topics discussed cover all areas of library activity. The assignments are the result of one's own professional work and knowledge, as well as the experience acquired during the training for the exam. The collection includes written papers of all candidates who have passed the exam.
To be able to perform professional librarian work independently, whether in a library, or other organization working in the field of librarianship, the employees are required to pass the national librarianship exam. On the basis of a public mandate, the examinations are organized and conducted by the National and University Library. The collection consists of written assignments prepared by the library employees for the purposes of the examination. A candidate prepares a written paper during the professional training for the examination, which takes place in the library under the guidance and supervision of a tutor. The written assignment for the librarian examination is an independently written dissertation of a selected professional topic referring to the field of librarianship. The topics discussed cover all areas of library activity. The assignments are the result of one's own professional work and knowledge, as well as the experience acquired during the training for the exam. The collection includes written papers of all candidates who have passed the exam.